Historical conditions in mixed-conifer forests on the eastern slopes of the northern Oregon Cascade Range, USA - Hagmann, R. Keala; Franklin, Jerry F.; Johnson, K. Norman (Forest ecology and management, 2014)
•Spatially extensive and intensive record of historical landscape-level variability.•Forests were predominantly low density, less than a quarter of current mean density.•Large trees (>53cm dbh) dominated basal area on 91% of sampled area.•Large trees were primarily ponderosa pine (>60%) and secondarily Douglas-fir (>30%).•Comparable densities and abundance of large trees across a wide moisture gradient. Historical forest conditions in frequent-fire forests may be increasingly useful in guiding contemporary forest management given (1) projections for increased drought stress associated with climate change and (2) increases in vertical and horizontal fuel connectivity related to changes in land use over the past 150years. Records from a 1922–25 timber inventory reveal historical variability at the landscape-level on mixed-conifer habitats on the eastern slopes of the Cascade Range in northern Oregon. Live conifers >15cm dbh (diameter at breast height) were tallied by species and diameter class in a 20% sample of over 50,000hectares (ha). Forests were predominantly low density (66tph, standard deviation=32, range=0–289) relative to current conditions (312±245, 0–1643tph). Historical basal area averaged 14±7 (0–70)m2ha−1. Total stand density, large tree (>53cm dbh) density, and ponderosa pine density were relatively stable across a wide moisture gradient (42–187cm annual precipitation). Large trees dominated total basal area (73±16%) and comprised 42±17% of total trees per hectare (tph). Ponderosa pine contributed 62±27% of basal area. Together, ponderosa pine and Douglas-fir constituted 91±15% of basal area. Large ponderosa pine and Douglas-fir were nearly ubiquitous across the landscape in this historical data set, occurring on 94% and 83% of transects respectively. Large grand fir occurred on 20% of transects but contributed only 2±6% to large tree basal area. Higher-density values (>120tph), although rare, were distributed throughout the mixed-conifer habitat while large (>1.6ha) treeless (no conifers >15cmdbh) areas were almost entirely restricted to higher elevation, colder, wetter habitat types. Currently ponderosa pine no longer dominates large tree basal area, large trees no longer dominate total basal area, and Douglas-fir is now the dominant species across the landscape. Current mean tree densities are more than four times greater than values recorded in the historical cruise, and current basal area is approximately two times greater. Currently, large trees dominate basal area on only 29% of area inventoried compared to 91% in 1922–25. This systematic sample of a large landscape provides information about variability in species composition, densities, and structures at multiple spatial scales, which are highly relevant to management activities to restore and conserve desired ecosystem functions. Forest conditions comparable to those in this historical record have demonstrated resilience and resistance to fire and drought-related stressors in other frequent-fire forests.